Proposed Marketing Strategy Smart Home Service PT Telekomunikasi Indonesia - Winanti, Winda; Desiana, Krisnati (The Indonesian Journal of Business Administration, 2014)
Abstract— PT Telekomunikasi Indonesia has stated 4 area growth of New Revenue Stream to support it’s TIMES (Telecommunication, IT Services, Media, Edutainment and Services) business portfolio, that is Mobile Broadband, Cloud Computing, Home Digital Environment, and Machine-to-Machine. PT Telekomunikasi Indonesia require product innovation within those four areas. One of the innovations is the Smart Home product that has two key words in the technology: Smart Home and Broadband. In terms of technology, Telkom has access network infrastructure, servers, platform technology, methodology, and technology development experience in product development and information technology-based services to customers nationwide. Telkom also has the experience and competence to establish cooperation with manufacturer partners to develop the Smart Home. On the other side, in terms of business, based on ON World Research 2011, Smart Home applications will increase up to 103% in the period 2010-2015 and the global demand for services will reach $ 6 billion by 2015. The objective of this final project is to provide suitable marketing strategies for PT Telekomunikasi Indonesia in order to support successful launch for Smart Home service. To provide a comprehensive evaluation, the assessments include macro analysis, industry analysis, competitor analysis, investment feasibility analysis, SWOT analysis, business model analysis, and market analysis.The root cause analysis has resulted in three areas of improvement: (1) Market knowledge of the Smart Home services remains low, that will becomes a problem that must be addressed by PT Telekomunikasi Indonesia to achieve the success of launching the Smart Home service; (2) Smart Home service has a fairly high needs from the market, but it is not followed by high interest as well, which can lead to failure of the marketing strategies implementation of Smart Home service; and (3) The concept of service offerings in the form of starter packs is considered less attractive to the market, therefore PT Telekomunikasi Indonesia should implement another concept of offering the service to achieve successful launch of Smart Home service.The recommendation on marketing strategy includes the application of bundling system that could divide the cost of purchasing the device in pricing strategy, cooperate with housing developers to be the distributor, and using office buildings and high class schools as facilities in distribution strategy. With the implementation of business solutions, PT Telekomunikasi Indonesia is expected to solve existing business problems. Key  Words: smart home, marketing strategy, market awareness, Integrated Marketing Communication.